A DEHP plasticizer alters synaptic proteins via peroxidation. Issue 1 (21st November 2016) - Wang, Shaohui; Zhang, Pengyan; Liu, Ruifang; Li, Yuan; Liu, Chao; Liao, Xiaomei
Graphical Abstract: Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a widely used commercial plasticizer. DEHP exposure has a negative impact on brain development and cognition, but the mechanisms responsible for DEHP-induced neurotoxicity are not well understood. Here we showed that DEHP exposure increased maleic dialdehyde and reactive oxygen species contents and decreased endogenous superoxide dismutase activity in a mouse neuroblastoma cell line (N2a cell line). DEHP exposure not only induced reduction of neurite outgrowth, but also led to microtubule-associated protein tau hyperphosphorylation and dissociation from microtubules. Furthermore, DEHP exposure decreased the levels of synapsin-1 and postsynaptic density protein 95 (PSD95), which play critical roles in synaptic function. Antioxidant vitamin E pretreatment prevented DEHP-induced abnormalities in the cells. These results indicate that DEHP exposure could induce abnormal action of proteins including tau, synapsin-1 and PSD95, which play critical roles in the synaptic structure and function, and that these alterations might be mediated by peroxidative damage.